Umami enhancing properties of enzymatically hydrolyzed mycelium of flammulina velutipes cultured on potato pulp - Happel, Katharina; Zeller, Lea; Hammer, Andreas Klaus; Zorn, Holger; Justus Liebig University Giessen (My University, 2025)
The aim of this study was to hydrolyze cultivated fungal mycelium and to evaluate the effect on its taste. Potato pulp, a by-product of the potato starch industry, was therefore successfully utilized as a substrate for submerged cultivation of Flammulina velutipes, yielding a product with an estimated fungal content of 83% ± 3%. The fermentation increased the protein content from 5.3 ± 0.4 g/100 g DM to 13.9 ± 0.1 g/100 g DM with a biological protein value of 86. The fermentate was enzymatically hydrolyzed by Corolase APC-peptidase. After optimization of the hydrolysis conditions, a degree of hydrolysis (DH) of 75.1% ± 1.0% was achieved. The protein hydrolysis increased the contents of free glutamate more than 20-fold from 8.7 ± 0.1 mg/L to 188.7 ± 1.2 mg/L. Elevated glutamate levels led to an umami taste perception in aqueous solution and taste-enhancing properties in vegetable broth. Noteworthy, the fermentate itself exhibited an intrinsic peptidase activity. Without addition of auxiliary peptidases, mycelial enzymes caused a DH of 33.9% ± 0.7% and a free glutamate content of 99.1 ± 0.7 mg/L. For these samples, an increase in umami taste was only observed in vegetable broth, but not in water, indicating taste-enhancing properties but low umami taste. In addition to the nutritional and health benefits of fungi, their hydrolysates are of great interest for use as a protein booster with flavor-enhancing properties.
Keywords: ddc:540